Psychiatric assessment of severe presentations in autism spectrum disorders and intellectual disability - King, Bryan H; de Lacy, Nina; Siegel, Matthew (Child and adolescent psychiatric clinics of North America, 2014)
Children with autism spectrum and related disorders and intellectual disability are not protected from the experience of psychiatric illnesses. Many factors can contribute to exacerbation of existing behavioral symptoms or to the emergence of new psychiatric problems. The psychiatric assessment must thus take into account a range of possible etiologic or contributory factors. The approach outlined in this article highlights the value of assessing 4 broad domains, including diagnostic (genetic) factors, medical considerations, developmental influences, and environmental factors. Examples of how the consideration of each of these domains may inform the diagnostic formulation are highlighted.